2023
DOI: 10.1007/s13744-023-01037-1
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Oil Encapsulated with Silica Nanoparticles: Chemical Characterization and Evaluation of Insecticidal Activity Against the Rice Moth, Corcyra cephalonica

Abstract: Cinnamon (Cinnamomum zeylanicum Blume) essential oil has vast potential as an antimicrobial but is limited by its volatility and rapid degradation. To decrease its volatility and prolong the efficacy of the biocide, cinnamon essential oil was encapsulated into mesoporous silica nanoparticles (MSNs). The characterization of MSNs and cinnamon oil encapsulated with silica nanoparticles (CESNs) was estimated. Additionally, their insecticidal activity against the rice moth Corcyra cephalonica (Stainton) larvae was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…This method has both advantages and disadvantages; it favors the persistence of the essential oils in the environment and the extension of their action time. But most of the toxicological tests carried out by researchers, especially in laboratory conditions but also in field conditions, had as their object the effect of oils administered, and as such (in different concentrations and by various methods), there are few studies comparing the effect of raw oil vs. encapsulated oil [4,60,146]. These studies, most of the time, revealed a considerable increase in the toxicity of the essential oils compared to the non-target, beneficial species, along with an increase in the toxic effect compared to the harmful insect species [60].…”
Section: Discussionmentioning
confidence: 99%
“…This method has both advantages and disadvantages; it favors the persistence of the essential oils in the environment and the extension of their action time. But most of the toxicological tests carried out by researchers, especially in laboratory conditions but also in field conditions, had as their object the effect of oils administered, and as such (in different concentrations and by various methods), there are few studies comparing the effect of raw oil vs. encapsulated oil [4,60,146]. These studies, most of the time, revealed a considerable increase in the toxicity of the essential oils compared to the non-target, beneficial species, along with an increase in the toxic effect compared to the harmful insect species [60].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings align with many other studies that have used SiNPs as insecticide carriers to boost their potency. It has been established that SiNP is a reliable and safe source of insecticides that may be employed at low and ecologically friendly dosages to control various other insect pests (Attia et al, 2023;Saw et al, 2023).…”
Section: Discussionmentioning
confidence: 99%